Responses of yellow catfish (Pelteobagrus fulvidraco Richardson) to low‐protein diets and subsequent recovery. (23rd August 2012) - Dong, G.F.; Yang, Y.O.; Yao, F.; Wan, Q.; Yu, L.; Zhou, J.C.; Li, Y.
Abstract: A 4‐week growth trial was conducted to investigate the effect of low‐protein diets on the growth and amino acid (AA) composition of yellow catfish, and subsequent recovery when the fish were then switched back to the control diet for a further 4 weeks. Three isolipidic and isocaloric diets containing 390 g kg −1 (Control), 320 g kg −1 (D320) and 260 g kg −1 (D260) graded protein levels were evaluated. During the protein restriction period, specific growth rate (SGR) of D320‐and D260‐treated fish was significantly reduced by 20.79% and 29.21% compared to the control fish, respectively ( P < 0.05), while significant improvements in protein retention efficiencies were observed in fish fed with the D320 (12.82%) and D260 (19.58%) diets ( P < 0.05). The D260‐treated fish had significantly lower (0.87%) whole‐body essential amino acid (EAA) and significantly higher (0.74%) non‐essential amino aci (NEAA) concentrations compared to the control fish. After a 4‐week realimentation, significant increases in the SGR of the protein‐restricted fish were observed. However, no significant differences in the whole‐body EAA or NEAA concentrations among groups were observed ( P > 0.05). The results indicate that previously protein‐restricted yellow catfish can compensate completely in terms of final body weight, growth rate and whole‐body AA concentrations.